2021
DOI: 10.1093/ofid/ofab216
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculitis: A Severe Complication of Central Nervous System Infections

Abstract: Background Ventriculitis, a dreaded complication of brain abscess, meningitis, and various neurosurgical procedures, has attracted limited attention in the medical literature. Methods Retrospective single-centre study. We screened medical files of all patients who had a brain imaging report including the word “ventriculitis” during years 2005-2019. Only patients with clinical, microbiological and imaging features of ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…An infected episode was defined as a patient who had clinical features of HCAVM ( 22 ) and an improvement related to a susceptible antimicrobial agent. However, the therapeutic effect of the susceptible antimicrobial agent alone could be deficient in patients with special situations, including poor wound healing ( 26 ), implants ( 27 ), CSF leakage ( 28 ), abscess ( 29 ), and ventriculitis ( 30 ). For episodes with two or more positive cultures, the first positive culture was analyzed ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…An infected episode was defined as a patient who had clinical features of HCAVM ( 22 ) and an improvement related to a susceptible antimicrobial agent. However, the therapeutic effect of the susceptible antimicrobial agent alone could be deficient in patients with special situations, including poor wound healing ( 26 ), implants ( 27 ), CSF leakage ( 28 ), abscess ( 29 ), and ventriculitis ( 30 ). For episodes with two or more positive cultures, the first positive culture was analyzed ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…Ventriculitis is associated with high rates of mortality and morbidity [1,12]. A recent, large case series demonstrated a mortality rate of 30% among patients with ventriculitis, though that cohort included patients without EVDs as well [2]. It is important to recognize that ventriculitis occurs in patients who are at elevated risk of mortality due to their underlying neurocritical condition (such as subarachnoid hemorrhage, traumatic brain injury); therefore, mortality in these patients is attributable to many reasons, one of which is ventriculitis.…”
Section: Why Does Ventriculitis Matter?mentioning
confidence: 99%
“…Ventriculitis complicating EVD insertion is associated with significantly longer hospital length of stay and cost of healthcare [13]. The risk of neurological impairment among survivors has increased five-fold [13], with Luque-Paz et al [2] reporting persistent, longterm neurological impairment in 62% of patients. Deficits included cognitive disorder, seizures, gait disturbance, fatigue, and memory loss.…”
Section: Why Does Ventriculitis Matter?mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study on bacterial meningitis in adults, the in-hospital mortality for patients with community-acquired or healthcare-related meningitis was 10.6%, which increased to 14.8% at three months after discharge [ 6 ]. Ventriculitis, also accounted among the CNS infections, is a severe complication of meningitis and brain abscess that frequently occurs after neurosurgical procedures [ 2 , 7 ]. A recent study found that ventriculitis has an in-hospital mortality rate of 30% and leads to neurological sequelae in 60% of survivors, highlighting the severity of this type of infection [ 7 ].…”
Section: Introductionmentioning
confidence: 99%